Estratégias de utilização do capim-andropógon - COSTA, Clésio dos Santos (2017)
The grass-andropogon is a perennial grass is well resistant to low fertility soils, to places that suffer water restriction as in the Northeast region. The objective of this study was to evaluate strategies for the use of andropogongrass during the rainy season. The structural and chemical characteristics were evaluated as a function of two defoliation intensities and rest periods. In the dry period the nutritive value of deferred andropogenic grass treated with ammonia. Experiment rains: two defoliation intensities (15 and 30 cm) and four rest periods (25, 35, 45 and 55 days) were evaluated in a completely randomized design in a factorial arrangement, with four replications. Depletion intensity did not affect dry leaf biomass (P> 0.05). The rest period provided a linear decreasing effect (P <0.05) on the biomass of dried leaf blades in the two defoliation intensities. It was observed that the intensity of 15 cm occurred a reduction of 19.52 kg of leaves for each day of rest, already in the intensity of 30 cm was registered a reduction of 35.41 kg for each day. The biomass of dry stalks showed an increasing linear effect (P <0.05) as a function of the rest periods in the two defoliation intensities. Production of 2427.71, 2907.39, 3325.72 and 3749.45 kg ha-1 was recorded for the periods of 25, 35, 45 and 55 days respectively. In the intensity of 30 cm, a reduction of 40.75 kg was recorded for each day of rest period. The rest period provided a linear decreasing effect (P <0.05) on the blade / stem ratio in the two defoliation intensities. A reduction of 0.02 and 0.03 was observed for each day of the rest period in intensities of 15 and 30 cm, respectively, the highest relation was observed with 25 days (1.39) and the lowest with 55 days (0. 64). The population density of tillers responded in a linear descending manner (P> 0.05) to the rest periods for the defoliation intensity of 15 cm, with a reduction of 2.59 tillers for each day over a rest period. For the intensity of 30 cm, no linear regression effect was observed (Y = 530.10). The height of the pasture was influenced by the rest periods, with values of 1.33, 1.82, 2.07 and 2.24 m recorded for the periods of 25, 35, 45 and 55 days respectively. The DM content presented an increasing linear effect (P <0.05) as a function of the rest periods evaluated in the two defoliation intensities. For each additional day in the rest period, an increase of 2.8 and 2.7 g / kg was recorded for the intensities of 15 and 30 cm, respectively. The rest period indicated a linear decreasing behavior (P <0.05) for PB content in the two defoliation intensities. A decrease of 0.9 and 0.7 g / kg was recorded for each day of rest period. For each day over the rest period an increase of 1.2 and 1.5 g / kg DM in the NDF content was recorded at intensities of 15 and 30 cm. It is recommended the use of managed andropogon grass with regrowth age of 25 days and height of residue of 15 cm. Dry experiment: For the chemical composition, a completely randomized design was used, with five treatments (0, 2, 4, 6, and 8% addition of urea in% of DM) and five replications. To evaluate the in situ degradation of DM, a fistulated sheep with a mean live weight of 60 kg was used. For the degradation, a completely randomized design was used in a 5 x 4 factorial arrangement (five urea levels x four incubation times 6, 24, 48 and 72). The ammonization provided a linear effect (P <0.05) for the DM content of the andropogon grass, a minimum level of 4.63 urea was recorded, and from this level the MS content increased again. There was a positive linear effect (P <0.05) for the crude protein (CP) contents, an increase of 15.07 g / kg of PB was observed for each 1% of urea added to the andropogon grass, the value of Protein obtained through the equation for the highest dose was 139.4 g / kg DM. The effect of ammonia on neutral detergent fiber (NDF), hemicellulose and acid detergent fiber (ADF) was observed, respectively, with a decrease of 10.45, 4.06 and 6.39 g / kg of DM respectively. The neutral detergent insoluble nitrogen content (NIDN) was negatively linear (P <0.05) as a function of ammonia. It was recorded that for each 1% of urea a reduction of 41.77 g / kg was observed. However, ash content did not show any effect (P> 0.05), values of 27.0, 31.8, 32.0, 36.1 and 36.6 g / kg DM were recorded at levels of 0, 2, 4, 6 and 8%, respectively. The soluble fraction of the andropogon grass increased as the ammonia levels increased (14.20, 16.19, 17.27, 19.23, 18.04%, to the levels of 0, 2, 4, 6 And 8%, respectively). It is recommended to use the addition of urea at the 4% level in the process of ammonization of the deferred andropgrass grass.